Spatiotemporal Impact on Vegetation by Tunnel Discharging in the Jinping II Hydropower Station: Evidence From the NDVI and GPP Monitoring Dataset of 2001–2019 - Song, Ci; Huang, Runqiu; Tang, Xiaolu (Frontiers in Earth Science, 2022)
An impact on vegetation by tunnel discharging has been a critical point for underground constructions around the world. The Jinping II hydropower station in China possesses the world’s largest karst diversion tunnel group and discharged massive groundwater during the construction period. This study assessed the effects on vegetation in the karst and non-karst areas at different stages before construction (2001–2003, BC), during construction (2004–2014, DC), and after construction (2015–2019, AC) based on the Normalized Difference Vegetation Index (NDVI) and the gross primary productivity (GPP) dataset of the moderate resolution-imaging spectroradiometer (MODIS). The regional median results of the NDVI and GPP showed that the whole vegetation was little changed by massive tunnel drainage throughout BC, DC, and AC. The NDVI and GPP were locally decreased in the first 3 years, and then recovered to the original level within next several years. Notably, the NDVI and GPP of the karst area (20 and 50% in the total area) were decreased more significantly than those of the non-karst area (8 and 20% in the total area). The factors controlling vegetation change are the development of karst and fractures, which are the conduits of groundwater flow. Therefore, massive groundwater discharge is the primary influence leading to the vegetation deterioration in the Jinping II hydropower station. The research would provide a vital reference for vegetation protection of large-scale underground construction in the world.